2023
DOI: 10.3390/life13020380
|View full text |Cite
|
Sign up to set email alerts
|

Juglans regia Linn.: A Natural Repository of Vital Phytochemical and Pharmacological Compounds

Abstract: Juglans regia Linn. is a valuable medicinal plant that possesses the therapeutic potential to treat a wide range of diseases in humans. It has been known to have significant nutritional and curative properties since ancient times, and almost all parts of this plant have been utilized to cure numerous fungal and bacterial disorders. The separation and identification of the active ingredients in J. regia as well as the testing of those active compounds for pharmacological properties are currently of great intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 102 publications
0
11
0
1
Order By: Relevance
“…During cold stress, the expansion of the stem's conductive and parenchymal tissues compared to the control is necessary to manage an increased flow of water and organic compounds. This adjustment leads to a higher total water content in the tissues of walnut microclones under cold stress, which may be an indicator of J. regia microclones' adaptation to cold [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…During cold stress, the expansion of the stem's conductive and parenchymal tissues compared to the control is necessary to manage an increased flow of water and organic compounds. This adjustment leads to a higher total water content in the tissues of walnut microclones under cold stress, which may be an indicator of J. regia microclones' adaptation to cold [58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Juglone (JUG, 7 , Figure ), 5-hydroxy-1,4-naphthoquinone, is an allelochemical found in walnut plants such as Juglans regia (J. regia) . Walnut extracts are widely used in folk medicine for treating arthritis, stomach aches, skin disorders, and infectious diseases. , Besides, JUG has been used as a natural dye and colorant in cosmetics and foods despite its potentially hazardous effects . Previous studies have shown the anticancer, anti-inflammatory, antidiabetic, and antiviral effects of JUG, , and a number of JUG derivatives have been synthesized and biologically evaluated. Recently, we have reported that JUG exhibited antiplatelet effects which were associated with inhibition of platelet surface PDI activity …”
Section: Introductionmentioning
confidence: 99%
“… 28 Walnut extracts are widely used in folk medicine for treating arthritis, stomach aches, skin disorders, and infectious diseases. 29 , 30 Besides, JUG has been used as a natural dye and colorant in cosmetics and foods despite its potentially hazardous effects. 31 Previous studies have shown the anticancer, anti-inflammatory, antidiabetic, and antiviral effects of JUG, 32 , 33 and a number of JUG derivatives have been synthesized and biologically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…There are over ten million cancer cases diagnosed each year throughout the world, and more than half of patients die from it [2,3]. Cancer ranks as the second leading cause of death in many countries after cardiovascular diseases [4,5]. Colorectal cancer (CRC) is a type of cancer that affects the colon (large intestine) and rectum [6].…”
Section: Introductionmentioning
confidence: 99%